THE IMPACT OF COMMUNICATION PSYCHOLOGY IN GUIDANCE SERVICES ON PILGRIMS’ TRUST TOWARD UMRAH TRAVEL AGENCIES - Irsyad Baitusslam, Muhammad; Dina Afiyah, Muhammad; Habsi, Malikul (International Journal of Multidisciplinary Reseach, 2025)
The rapid expansion of the Umrah industry has intensified the need for high-quality guidance services that address both the logistical and psychological dimensions of pilgrimage preparation. This study investigates the impact of communication psychology on pilgrims’ trust toward Umrah travel agencies, focusing on key communicative elements such as empathy, message clarity, emotional support, responsiveness, and guide credibility. Using a quantitative explanatory design, data were collected from 268 Indonesian pilgrims through validated Likert-scale questionnaires and analyzed using PLS-SEM. The findings show that communication psychology is applied effectively within guidance services and significantly enhances pilgrims’ trust. Empathic interaction, understandable ritual explanations, emotional regulation, and interpersonal warmth create a supportive learning environment that reduces anxiety and increases confidence. Communication behavior that reflects credibility, transparency, and genuine care also strengthens perceptions of agency integrity and reliability. These results confirm that psychological aspects of communication play a critical role in trust formation, complementing operational service quality. The study fills an important research gap by empirically modeling communication psychology as a multidimensional predictor of trust in Umrah services and offers practical implications for agency training programs aimed at improving guide competence and pilgrims’ overall experience.